Energy expenditure of young race cyclists at different stages of the training process - Dondukovskaya, R.; Pshendin, A.; Cherenina, S. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
One of the most important problems for the organization of young sportsmen rational nutrition is the determination of daily energy requirements. The objective of the present study was to investigate energy expenditure depending on stage of the training process in young cyclists from the Sports Centre of the College of Olympic Reserve. The pedagogical tasks for young bicyclists training are to set up two basic micro cycles in training: preparatory period and period of competition, which essentially differ in character and intensity of performed exercises. Purpose The purpose of this work consists in investigation of energy expenditure in young cyclists depending on stages of training. The object of research is presented in table 1. Methods Gas exchanges were determined during exercises on a cycle ergometer consisting of 6 steps of 3 minutes with increasing power by 50 W per step. The sportsmen`s consumption of oxygen was monitored (Spirolit gasmeter) at standard values of heartbeat measured by telemetric monitor of HR (POLAR ELECTRO). Daily energy requirements were assessed from daily energy expenditure using a factorial method. Basal metabolic rate (BMR) was predicted using the Harris-Benedict (1919) equations. Energy expenditure corresponding to each activity was calculated as BMR (kcal/min) multiplied by the corresponding physical activity ratio (PAC) and the time spent at each activity during the whole day. The latter was assessed from an activity diary (number of minutes for each type of activity) filled during ten days of training. Daily energy expenditure was the sum of energy expenditures associated with various activities. For calculation of energy expenditure at different stages of training we used data on oxygen consumption (1LO2 = 5kcal) measured at the cycle ergometer, pulse rate charts (pulse taken during 10 beat/min fold time) and training time. The weekly workload for boys during preparation was 425.2±16.4 km, during competition stage it was 545.8±24.5 km and for girls 361.4±15.7 km and 487.6± 18.1 km respectively. Results Periods of training essentially differ by character and intensity of performed exercises. In the preparatory period stamina improving exercises take significant place. Usually this work corresponds to heart beat rate of 130-140 per min. on average. In the period of competition interval method was used that usually corresponds to heart beat rate of 140-160 per min on average. On the assumption that nutrition calorie content should exceed power expenditure by 10%, energy requirements for young cyclists in sport boarding schools were calculated (table 2). Conclusion Daily energy requirement of the 14-16 year-old boys averaged 4580 and 5050 kcal during the preparation and the competition periods, respectively. The corresponding requirements of the 14-16 year-old girls were 2960 and 3300 kcal, respectively. Thus, for the optimal nutrition of young race cyclists it is necessary to take into account age, sex, anthropometric characteristics, training stage and work load in order to calculate energy, macronutrient and micronutrient requirements.